Improving Ipa Students’ Achievement In Green Growth Materials At The Fifth Grade Students Through Cooperative Learning Method Type Stad In Sdn 06 Perawang Barat 2013/ 2014 - Arianis Arianis (Fakultas Sastra Universitas Ekasakti, 2017)
Teachers make various efforts to improve student learning outcomes. Therefore, it is needed a learning action that can enliven the students' motivation in achieving good values, individually or in groups. One way is to implement cooperative learning. In this learning students are required to work together in small groups to solve a problem and the group's primary goal is toward success. STAD type cooperative learning is based on an idea where students work together in a group and participate personally in the learning activities of their group members. Based on the background of the problems can be formulated as follows: